Bacterial synthesis of silicon/silica nanocomposites - Singh, Sanjay; Bhatta, Umananda M.; Satyam, P. V.; Dhawan, Alok; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
The synthesis of silicon/silica nanoparticle composites by the bacterium Actinobacter sp. is demonstrated. More specifically, the formation of silicon/silica nanocomposite is shown to occur when the bacterium is exposed to K(2)SiF(6) precursor under ambient conditions. Based on the earlier reports where this bacterium has been shown to synthesize iron oxide and iron sulfide nanoparticles, it is hypothesized that this bacterium secretes reductases and oxidising enzymes, which lead to the Si/SiO(2) nanocomposite synthesis. The particles obtained by bacterial synthesis were thoroughly characterized. The cytotoxicity studies revealed that the particles do not display any cytotoxicity to human skin cells. The synthesis of silica nanoparticles by bacteria in the present study demonstrates the versatility of the organism, and the formation of elemental silicon by this environmentally friendly process expands further the scope of microorganism based nanomaterial synthesis.

Bacterial synthesis of phtocatalytically active and biocompatible TiO2 and ZnO nanoparticles - Singh, Sanjay; Britto, Virginia D.; Bharde, Atul A.; Sastry, Murali; Dhawan, Alok; Bhagavatula L. V. Prasad (International Journal of Green Nanotechnology: Physics and Chemistry, 2010)
TiO2 and ZnO nanoparticles are well known for their photocatalytic and ultraviolet (UV)-absorbent properties and have successfully entered into the market as consumer products. Large volume production of these nanoparticles by industries require environmentally friendly processes of synthesis. In this article, we show that when challenged with an appropriate precursor, the bacterium Actinobacter spp. can lead to the extracellular synthesis of ZnO and TiO2 nanoparticles. The biological way of synthesizing these materials probably leads to the in situ doping of elements like C, F, and N into their crystal lattices, which is evidenced by a red shift in the absorption edge. Because the doping is expected to affect the photocatalytic activity of these materials under different light conditions, such investigations have also been undertaken here. Further, the biocompatibility of these nanomaterials (cytotoxicity and genotoxicity) has also been investigated in detail.
Keywords: Biosynthesis; genotoxicity; Nanoparticles; Nanotoxicity; Photocatalysis

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.